LOS FUNDAMENTOS DE LA VIABILIDAD DEL APERCIBIMIENTO DE DENUNCIA DE OMISIÓN A LA ASISTENCIA FAMILIAR EN PROCESOS DE EJECUCIÓN - Alafaro Moreno, LOURDES MARINA (2018)
This investigation focuses in determinate the omission of family assistance’s criminal complaint in the proceedings of Execution of extra-judicial conciliation of maintenance agreement; since in legal courts of peace the plaintiff requests the variation of the warning of an Execution enforced by the seizure of property of the defendant to the warning of Criminal complaint due to Omission to Family Assistance. In response to this request, the judges mostly grant what the plaintiff asked for without giving enough reasons that explain their decision.